PENERAPAN MODEL BERMAIN PERAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA SEKOLAH DASAR NEGERI DI KECAMATAN NISAM ANTARA - Nazaruddin, Nazaruddin; Muharramsyah, Rambang; Iqbal, Muhammad (Dharmas Education Journal (DE_Journal), 2024)
The background to this research is the low learning achievement in Social Sciences Theme 3 Figures and Inventions sub theme 1 Inventors who changed the world in class VI of SD Negeri 7 Nisam Antara. Apart from that, students' motivation and learning activities are still low because teachers only use conventional models in learning. Based on these problems, researchers apply the Role Playing learning model. as an effort to improve student learning achievement. This research is Classroom Action Research. The subjects of this research were 20 class VI students at SD Negeri 7 Nisam Antara for the 2022/2023 academic year. The research was carried out in 3 cycles, each cycle consisting of 2 meetings. The data sources in this research are class VI students, class teachers, and document data. The data collected is qualitative data covering student learning activities and teacher performance, and quantitative data includes student academic performance, class average, and classical learning completion. Data collection techniques include tests and non-tests which include observation and recording. Data collection tools include tests and observation sheets. A research is declared successful if student academic performance and teacher performance in student learning activities increase according to the predetermined success indicators. The results of cycle-by-cycle research can be concluded that the Role Playing learning model can improve student learning achievement, class average, classical learning completeness, and learning activities for class VI students at State Elementary Schools in Nisam Antara District.